BEST INTERESTS OF THE MIGRANT CHILDREN IN THE SYSTEM OF ASYLUM IN THE REPUBLIC OF SERBIA - Novaković, Uroš (Serbian political thought, 2025)
In all the proceedings where the child appears as a party, the principle of the best interests of the child appears as the most general principle through which the child is protected. The following laws regulate the best interests of migrant children in the Republic of Serbia: Family Law, Law on Foreigners, Law on Asylum and Temporary Protection, and Law on Social Protection. One of the problems in practice is that an unaccompanied child, from entering the territory of Serbia until the submission of the asylum application, is assigned different persons as temporary guardians on several occasions. The major problem in the administrative procedure and the realization of the best interests of the child is reflected in the fact that police officers register unaccompanied and separated children and conduct official actions in the asylum procedure without the presence of a temporary guardian. Processing of asylum applications is not a priority, and the speed of decision-making depends on many factors, including the expediency of the acting official of the first instance body. The Asylum Office must take into account the best interests of the child at every stage of the asylum procedure, particularly when deciding on the child's asylum application, and must take into account the opinion of the guardianship authority and the opinion of the child, which is one of the basic elements of the principle of the best interests of the child.
Keywords: administrative proceeding; asylum; best interests of the child; child; migration